2019
DOI: 10.33549/physiolres.933992
|View full text |Cite
|
Sign up to set email alerts
|

MENS-associated increase of muscular protein content via modulation of caveolin-3 and TRIM72

Abstract: Microcurrent electrical neuromuscular stimulation (MENS) is known as an extracellular stimulus for the regeneration of injured skeletal muscle in sports medicine. However, the effects of MENS-associated increase in muscle protein content are not fully clarified. The purpose of this study was to investigate the effects of MENS on the muscular protein content, intracellular signals, and the expression level of caveolin-3 (Cav-3), tripartite motif-containing 72 (TRIM72) and MM isoenzyme of creatine kinase (CK-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…The mechanisms associated with this training-induced effect optimization are still unclear but they can be linked to an increased muscle membrane sensitivity in response to mechanical stimulus favoring a more efficient upregulation of muscle protein synthesis and recovery after each singular workout (Ohno et al 2013; Fujiya et al 2015). In fact, the application of microcurrent in mouse cell culture upregulated the expression of MM creatine kinase, Caveolin-3 and tripartite motifcontaining 72, which are proteins related to muscle growth and remodeling (Ohno et al 2019). Additionally, a transient increase in the relative expression of protein kinase B (p-Akt), which supports the promotion of muscle anabolism and the reduction of protein degradation via mTORC1 (Morley 2016) was also reported (Ohno et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanisms associated with this training-induced effect optimization are still unclear but they can be linked to an increased muscle membrane sensitivity in response to mechanical stimulus favoring a more efficient upregulation of muscle protein synthesis and recovery after each singular workout (Ohno et al 2013; Fujiya et al 2015). In fact, the application of microcurrent in mouse cell culture upregulated the expression of MM creatine kinase, Caveolin-3 and tripartite motifcontaining 72, which are proteins related to muscle growth and remodeling (Ohno et al 2019). Additionally, a transient increase in the relative expression of protein kinase B (p-Akt), which supports the promotion of muscle anabolism and the reduction of protein degradation via mTORC1 (Morley 2016) was also reported (Ohno et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the application of microcurrent in mouse cell culture upregulated the expression of MM creatine kinase, Caveolin-3 and tripartite motifcontaining 72, which are proteins related to muscle growth and remodeling (Ohno et al 2019). Additionally, a transient increase in the relative expression of protein kinase B (p-Akt), which supports the promotion of muscle anabolism and the reduction of protein degradation via mTORC1 (Morley 2016) was also reported (Ohno et al 2019). In this context Kwon et al (2017) observed beneficial effects of a short-term 40 min microcurrent treatment to improve handgrip strength, lower body endurance and muscular efficiency in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, on the other hand, the total protein content in C2C12 myotubes was decreased by MBNL1 knockdown. In general, total protein content increases, accompanying myotube growth and differentiation [32][33][34]. Therefore, the decrease of total protein content induced by MBNL1 knockdown might indicate a decrease in the cytoplasmic protein contents in myotubes without any structural changes.…”
Section: Discussionmentioning
confidence: 99%